Effect of acetylsalicylic acid on fibrin clot stability depending on factor XIII Val34Leu polymorphism - Brożek, Jan (2005)
Background Clinical observations suggest association of FXIII Val34Leu with lower odds of thromboembolic events, but basic research shows higher FXIII activation and resistance to fibrinolysis in Leu34 carriers. ASA inhibits FXIII activation more in Leu34 carriers. Aims To clarify effect of ASA on FXIII activation, clot permeability, and fibrinolysis resistance depending on FXIII Val34Leu polymorphism. Patients 9 healthy volunteers. Intervention ASA 300 mg. Methods At baseline and 4 h after ASA intake FXIII activation, γ dimer concentration in clots, fibrin gel permeability, and resistance to fibrinolysis after tPA were assessed in tissue factor-dependent coagulation model. Results FXIII activation was slower after ASA; effect was larger in Leu34 carriers. γ dimer concentration in plasma clots was lower after ASA and changed more in Leu34Leu homozygotes. Fibrin gel was more permeable after ASA; effect was larger in Leu34 homozygotes. Fiber diameter and mass/length ratio from permeability were increased following ASA; effect was larger in Leu34 homozygotes. Gel turbidity increased after ASA and change was greater in Leu34 homozygotes. Max fibrinolysis rate and 50% lysis time increased after ASA. Lysis was faster and 50% lysis time was shorter in Leu34 homozygotes. Conclusions In healthy individuals ASA 300 mg delayed activation of FXIII and made fibrin gel more permeable and pro
Keywords: polymorphizm; fibrin; factor XIII; Val34Leu; acetylsalicylic acid